2021
DOI: 10.2147/ott.s325203
|View full text |Cite
|
Sign up to set email alerts
|

CBX7, a Potential Prognostic Biomarker in Lung Adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is a major type of NSCLC and has high morbidity and mortality. The identification of useful prognostic biomarkers for LUAD is important. CBX7 has been reported in various cancers yet its expression level and potential roles have not been fully understood. Methods GEPIA, Oncomine, TCGA, KM plotter and OSluca databases were used to explore the expression profile and prognostic effects of CBX7 mRNA expression in patients with LUAD. TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Among known immunotherapy predictive biomarkers such as PD-L1, PD-1, CTLA-4, and TMB, as well as potential biomarkers predicted by the current studies, such as AUNIP, NPM1, EXO1, CBX7, and SFTPA1, increased AUNIP, NPM1, and EXO1 expression predicted worse OS in LUAD patients ( 68 - 70 ). In contrast, higher SFTPA1 and CBX7 expression predicted better outcome in LUAD patients ( 71 , 72 ). Comparing them with the IRGPI risk score, we found that the IRGPI score significantly correlated with these biomarkers, except for PD-L1.…”
Section: Discussionmentioning
confidence: 90%
“…Among known immunotherapy predictive biomarkers such as PD-L1, PD-1, CTLA-4, and TMB, as well as potential biomarkers predicted by the current studies, such as AUNIP, NPM1, EXO1, CBX7, and SFTPA1, increased AUNIP, NPM1, and EXO1 expression predicted worse OS in LUAD patients ( 68 - 70 ). In contrast, higher SFTPA1 and CBX7 expression predicted better outcome in LUAD patients ( 71 , 72 ). Comparing them with the IRGPI risk score, we found that the IRGPI score significantly correlated with these biomarkers, except for PD-L1.…”
Section: Discussionmentioning
confidence: 90%
“…Chromobox 7 (CBX7), is a member of the chromobox family. It has been reported to involve in oncogenesis, which may be deregulated in gliomas ( Bao et al, 2017 ), breast cancer ( Kim et al, 2015 ), cervical carcinoma ( Maimaitirexiati et al, 2021 ), lung cancer ( Yang et al, 2021 ), etc. Studies have shown that CBX7 can participate in maintaining the growth of a variety of normal cells and immortalizing mouse fibroblasts ( Jung et al, 2019 ), but the controversy about its role persists.…”
Section: Discussionmentioning
confidence: 99%
“…CBX6 may be either a poor prognostic factor or a favorable prognostic factor, depending on the type of cancer (67,77,94,(96)(97)(98)(99)103,110,117,122). CBX7 acts as a tumor suppressor in glioma (68), BC (15,77), LUAD (83,84,125), HCC (114,119), PAAD (99,109), ccRCC (110), CCA (112), sarcoma (106) and SKCM (113). When the expression of CBX7 is low, the OS of patients is shorter, but its relationship to survival in EC (86)(87)(88) and GC (94-98) is controversial.…”
Section: Othersmentioning
confidence: 99%